Individual Muscle Adaptations in different Resistance Training Systems in Well-Trained Men - Angleri, Vitor; Ugrinowitsch, Carlos; Libardi, Cleiton Augusto (International Journal of Sports Medicine, 2021)
Using a within-subject design we compared the individual responses between drop-set (DS) vs. traditional resistance training (TRAD) (n=16) and crescent pyramid (CP) vs. TRAD (n=15). Muscle cross-sectional area (CSA), leg press and leg extension 1 repetition maximum (1-RM) were assessed pre and post training. At group level, CSA increased from pre to post (DS: 7.8% vs. TRAD: 7.5%, P=0.02; CP: 7.5% vs. TRAD: 7.8%, P=0.02). All protocols increased the 1-RM from pre to post for leg press (DS: 24.9% vs. TRAD: 26.8%, P < 0.0001; CP: 27.3% vs. TRAD:2 6.3%, P < 0.0001) and leg extension (DS: 17.1% vs. TRAD: 17.3%, P < 0.0001; CP: 17.0% vs. TRAD: 16.6%, P < 0.0001). Individual analysis for CSA demonstrated no differences between protocols in 15 subjects. For leg press 1-RM, 5 subjects responded more to TRAD, 2 to DS and 9 similarly between protocols. In TRAD vs. CP, 4 subjects responded more to CP, 1 to TRAD and 10 similarly between protocols. For leg extension 1-RM 2 subjects responded more to DS, 3 to TRAD and 11 similarly between protocols. Additionally, 2 subjects responded more to CP, 2 to TRAD and 11 similarly between protocols. In conclusion, all protocols induced similar individual responses for CSA. For 1-RM, some subjects experience greater gains for the protocol performed with higher loads, such as CP.
Keywords: drop-set; crescent pyramid; volume load; one-repetition maximum; muscle cross-sectional area